Introduction to Raspberry Pi (LiveLessons., 2015)
"The hands-on video guide to Raspberry Pi: the tiny $35 computer that's changing the world! Use Raspberry Pi to learn programming and electronics, create Internet-connected projects, even build your own media server! These easy video tutorials are the fastest way to get started with Raspberry Pi, the $35 credit-card sized computer that's taking the world by storm! Raspberry Pi LiveLessons walks you through understanding the hardware, getting started, controlling your Pi, installing applications, creating electronics projects, building media servers, and more! Top Raspberry Pi instructor John LeMasney begins by touring Pi's components, explaining what it can do, and showing how it's similar to other computers--and how it's different. Next, he guides you through installing and exploring the powerful Raspbian Linux-based operating system and new applications...starting to program with the simple Scratch environment and the powerful Python language...using your Raspberry Pi to create images, edit photos, and design visual documents...experimenting with electronic circuits...even using your Pi as a portable, low-cost media server."--Resource description page.